Trends and Knowledge Gaps In Fish-Based Fermented Foods: A Bibliometric Analysis From The Last Decade (2015-2024) - Mamangkey, Jendri; Grovy Naibaho, Frans; Rosenta Purba, Ika; Yusriya Hibatullah, Alnadia; Aryanti Pada Soa, Christina (International Journal of Science, Technology & Management, 2025)
Fish-based fermented foods are integral to traditional diets across Asia, Africa, and Europe, valued for both their nutritional role and cultural significance. Increasingly, they are also studied for potential functional properties such as probiotic activity and bioactive compounds, yet their global research landscape has not been systematically assessed. This study presents a bibliometric analysis of global research on fish-based fermented foods published between 2015 and 2024. Data were retrieved from the Scopus database and analyzed using the Bibliometrix R package and Biblioshiny interface. A total of 263 documents were identified across 145 sources, authored by 1,150 researchers. The field has shown rapid growth, with an annual publication increase of 27.01% and an average of 28.48 citations per article, indicating strong scholarly visibility. Most contributions originated from East and Southeast Asia, particularly China, South Korea, and Thailand, reflecting the cultural and culinary importance of fermented fish in these regions. Author productivity followed Lotka’s law, with a small group of core researchers driving sustained output. Keyword co-occurrence and thematic mapping revealed dominant clusters around fermented fish sauce, lactic acid bacteria, and microbial diversity, alongside emerging themes related to fatty acids and bacterial communities. Despite these advances, the analysis highlighted notable gaps, including limited international collaboration and underrepresentation of research from Africa and parts of South Asia. These findings suggest that while the field is expanding and diversifying, greater cross-regional engagement and methodological innovation are needed to fully explore the nutritional, functional, and socio-economic dimensions of fish-based fermented foods.